OPTIMALISASI TREN INVESTASI GENERASI Z PADA AMGPM RANTING SION DALAM ERA DIGITAL: STRATEGI LITERASI KEUANGAN UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT : OPTIMALISASI TREN INVESTASI GENERASI Z PADA AMGPM RANTING SION DALAM ERA DIGITAL: STRATEGI LITERASI KEUANGAN UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Patty, Martha Racwel; de Fretes, Anna Valensia Christianty; Kurniawan, Sabda (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
This program was designed to improve the financial literacy of Generation Z, with a specific focus on members of the Maluku Protestant Church Youth Movement (AMGPM) in Poka Village. Initial assessments indicated that most participants had limited financial knowledge, with fewer than 30% understanding basic investment concepts. The initiative employed socialization and simulation methods to educate participants on investment principles, introduce regulated investment applications approved by OJK and BAPPEBTI, and promote secure online investment strategies. Evaluation findings revealed significant progress, with 40% of participants showing improved financial literacy. Additionally, over 75% successfully performed investment steps during simulations, and 85% expressed increased confidence in beginning their investment journey. While the program effectively enhanced participants' understanding, continued training is necessary to ensure long-term impact, particularly in the areas of portfolio diversification and risk management, which are critical for building sustainable and resilient investment practices.